Minimum Wage and Structural Poverty: A Mediation Analysis Based on Labor Market Theory in Jambi Province - Siswoyo, Siswoyo; Mainita, Mainita; Putra, Adi; Pasla, Bambang Niko (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
This study aims to analyze the effect of the Provincial Minimum Wage (UMP) on poverty in Jambi Province by examining the mediating role of the open unemployment rate. The minimum wage is a policy instrument used to enhance public welfare by increasing workers' income. However, in practice, increases in the UMP do not always lead to a direct reduction in poverty, particularly when labor market dynamics do not support wage policy impacts. From 2014 to 2023, the UMP in Jambi Province rose from IDR 1,502,230 to IDR 2,943,033. Nevertheless, poverty rates fluctuated, peaking in 2020 at 288,100 people and declining to 280,680 in 2023. These fluctuations suggest that the rise in the minimum wage has not produced a consistent effect on poverty reduction State the problem or phenomena studied in this paper and specify the research question(s) in one sentence. This study uses a quantitative approach and employs mediation analysis with the help of SPSS software. The results show that the UMP has a significant negative effect on open unemployment (β = –0.0005; p = 0.012), and open unemployment significantly increases poverty (β = 5.700; p = 0.031). The direct effect of UMP on poverty becomes insignificant when mediated by unemployment (β = 0.0025; p = 0.082). The indirect effect is statistically significant (–0.00285; 95% CI [–0.0051, –0.0009]). Open unemployment fully mediates the relationship between UMP and poverty. Therefore, the effectiveness of UMP policy in reducing poverty highly depends on the government's success in creating sufficient employment opportunities.